2016
DOI: 10.1038/emi.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of pre-epidemic and epidemic Zika virus strains for virological factors potentially associated with the rapidly expanding epidemic

Abstract: Less than 20 sporadic cases of human Zika virus (ZIKV) infection were reported in Africa and Asia before 2007, but large outbreaks involving up to 73% of the populations on the Pacific islands have started since 2007, and spread to the Americas in 2014. Moreover, the clinical manifestation of ZIKV infection has apparently changed, as evident by increasing reports of neurological complications, such as Guillain–Barré syndrome in adults and congenital anomalies in neonates. We comprehensively compared the genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
181
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 57 publications
(65 reference statements)
6
181
2
Order By: Relevance
“…42 Lanciotti et al 45 have shown that the Uganda MR766 ZIKV and the Yap Island Zika strains have 96% conservancy in their protein sequences, which the authors suggest could be the result of selective pressures arising from virus replication adapted to vertebrate hosts and arthropod vectors. This is also borne out by the Ka/Ks (asynonymous to synonymous) ratios for the various coding regions of ZIKV computed by Zhu et al 35 which showed that these ratios for ZIKV strains were comparatively low, implying that these genes were under stabilizing selection pressure. Note, however, the observations of Giri et al 46 from their study of the ZIKV proteome (strain MR766) that revealed abundant intrinsically disordered regions in the capsid, NS2B, NS3, NS4A and NS5 proteins …”
Section: Genetics Of Zikvmentioning
confidence: 99%
See 3 more Smart Citations
“…42 Lanciotti et al 45 have shown that the Uganda MR766 ZIKV and the Yap Island Zika strains have 96% conservancy in their protein sequences, which the authors suggest could be the result of selective pressures arising from virus replication adapted to vertebrate hosts and arthropod vectors. This is also borne out by the Ka/Ks (asynonymous to synonymous) ratios for the various coding regions of ZIKV computed by Zhu et al 35 which showed that these ratios for ZIKV strains were comparatively low, implying that these genes were under stabilizing selection pressure. Note, however, the observations of Giri et al 46 from their study of the ZIKV proteome (strain MR766) that revealed abundant intrinsically disordered regions in the capsid, NS2B, NS3, NS4A and NS5 proteins …”
Section: Genetics Of Zikvmentioning
confidence: 99%
“…Freire et al 38 also observed high levels of secretion of NS4A proteins, like for NS1 proteins, by infected cells, which they believe is significant since both NS1 and NS4A play important roles in viral replication, while NS4A helps viral survival by inhibiting cell death by up-regulation. Zhu et al 35 suggest that NS1 is required to initiate RNA genome synthesis.…”
Section: The Zikv Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The virus projects a glycosylation site outward and glycans are attached to the viral protein surface at this site. Thus, differences in carbohydrate molecules in this region may influence virus transmission and explain its tissue tropism or variable disease progression in different parts of the world [72]. Furthermore, glycosylation is a promising investigation target in context of potential receptors for anti-adhesive therapies.…”
Section: Zika Virusmentioning
confidence: 99%